Living Arrangements and Self-Study Time Associated with Ordinary Differential Equations Written-Solution Quality - Setiawan, Erwan; Zuber, Zuber; Inayah, Sarah (Universitas Suryakancana, 2025)
This study describes the association between students’ living arrangements and self-study time with the quality of written solutions in an Ordinary Differential Equations (ODE) course. A descriptive-exploratory quantitative approach was conducted with 18 sixth-semester pre-service mathematics teachers. Data were obtained from final ODE grades, an online questionnaire on living arrangements and estimated weekly self-study hours, and students’ written responses to four representative ODE problems (non-exact, first-order linear, Bernoulli, and an exact equation with an initial value). Solution quality was coded into four categories: complete-correct, conceptual error, procedural/calculation error, and blank. Descriptive and correlational analyses were used to identify trends among variables. Results indicate a positive correlation between self-study time and the proportion of complete-correct solutions (r = 0.4635) and a negative correlation with conceptual errors (r = ?0.3681). The proportion of complete-correct solutions also shows a strong correlation with the final ODE grade (r = 0.8945). These findings highlight the importance of structured support for self-study and diagnostic assessment based on error types to improve students’ understanding in ODE learning.